HUBUNGAN STADIUM PENYAKIT DENGAN KESEJAHTERAAN SPIRITUAL PASIEN KANKER PAYUDARA: HUBUNGAN STADIUM PENYAKIT DENGAN KESEJAHTERAAN SPIRITUAL PASIEN KANKER PAYUDARA - Afifah, Vina Asna; Sari, Ilma Widiya; Nofiah, Niafatun (LPPM STIKes Bahrul Ulum Jombang, 2020)
Spiritual well-being is an important thing that needs to be considered for breast cancer patients. Low spiritual well-being can make patients hopeless and feel insignificant, especially when the disease stage begins to develop into an advanced stage. The purpose of the study to know the relationship disease stage and spiritual well-being of breast cancer patients. The design of research used a cross sectional approach. The sampling technique used purposive sampling as many as 32 respondents. The results showed that 24 respondents (75%) were in stage 3 and spiritual well-being in the moderate category was 22 respondents (68.8%). Spearman rho correlation test showed a significant relationship between disease stage and spiritual well-being of breast cancer patients (p value 0.028 < 0.05) with a correlation coefficient of -0.389. The conclusion that there was a relationship between the stage of the disease and the spiritual well-being of breast cancer patients with a sufficient correlation value and has a negative correlation meaning that the lower stage of the disease, so the spiritual well-being of breast cancer patients will be better. Results of this study, respondents were hoped that could maintained their health and complied the therapy program so that the stage of the disease does not get worse, besides that respondents were expected to be able to get closer to God Almighty so that spiritual well-being will be better.